2013
DOI: 10.1093/mnras/sts685
|View full text |Cite
|
Sign up to set email alerts
|

The sub-stellar birth rate from UKIDSS★

Abstract: We present a new sample of mid L to mid T dwarfs with effective temperatures of 1100 to 1700 K selected from the UKIDSS Large Area Survey and confirmed with infrared spectra from X-Shooter/VLT. This effective temperature range is especially sensitive to the formation history of Galactic brown dwarfs and allows us to constrain the form of the sub-stellar birth rate, with sensitivity to differentiate between a flat (stellar like) birth rate, and an exponentially declining form. We present the discovery of 63 new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 84 publications
3
49
0
Order By: Relevance
“…However, close inspection reveals specific discrepancies near 1.3 and 1.6 μm, and a subtle "dip" feature at 1.62 μm. Such features have been previously noted in the combined-light spectra of very low mass spectral binary systems with late-type M or L dwarf primaries and T dwarf secondaries (e.g., Cruz et al 2004;Burgasser 2007b;Burgasser et al 2010Burgasser et al , 2011Burgasser et al , 2012Gelino & Burgasser 2010;Kirkpatrick et al 2012;Day-Jones et al 2013;Deacon et al 2014;Bardalez Gagliuffi et al 2014). To assess whether WISE J0720-0846 is such a system, we used the fitting method described in Burgasser et al (2010), comparing the spectrum of WISE J0720-0846 to 699 single star templates and 107,646 binary templates from the SPL.…”
Section: Identification As a Spectral Binarymentioning
confidence: 98%
“…However, close inspection reveals specific discrepancies near 1.3 and 1.6 μm, and a subtle "dip" feature at 1.62 μm. Such features have been previously noted in the combined-light spectra of very low mass spectral binary systems with late-type M or L dwarf primaries and T dwarf secondaries (e.g., Cruz et al 2004;Burgasser 2007b;Burgasser et al 2010Burgasser et al , 2011Burgasser et al , 2012Gelino & Burgasser 2010;Kirkpatrick et al 2012;Day-Jones et al 2013;Deacon et al 2014;Bardalez Gagliuffi et al 2014). To assess whether WISE J0720-0846 is such a system, we used the fitting method described in Burgasser et al (2010), comparing the spectrum of WISE J0720-0846 to 699 single star templates and 107,646 binary templates from the SPL.…”
Section: Identification As a Spectral Binarymentioning
confidence: 98%
“…We searched DwarfArchives (update of 6th of November 2012) for known L and T dwarfs with 13.0 < J < 17.5 in the UKIDSS LAS Y JHK footprint, supplemented by the recent samples of Burningham et al (2013), Day-Jones et al (2013), Kirkpatrick et al (2011), and Mace et al (2013). A few sources with unreliable photometry in any of the eight bands (e.g.…”
Section: Possible Sources Of Bias In the Colour Relationsmentioning
confidence: 99%
“…A good example of the state of the art in obtaining a statistical sample of brown dwarfs is the study of the sub-stellar birth rate by Day-Jones et al (2013). They classified 63 new L and T dwarfs brighter than J = 18.1, using X-shooter spectroscopy on the Very Large Telescope (VLT), after selecting them through colour cuts.…”
Section: Introductionmentioning
confidence: 99%
“…Large samples have revealed the mass and luminosity functions of the local ultracool population (e.g., Allen et al 2005;Cruz et al 2007;Burningham et al 2010b). Measurements of the space density of brown dwarfs (e.g., Metchev et al 2008;Reid et al 2008) have identified a relative paucity of L/T transition dwarfs, indicating that this evolutionary phase is short-lived and constraining the birth history of substellar objects (e.g., Day-Jones et al 2013;Marocco et al 2015). The surveys have also enhanced brown dwarf searches in star-forming regions (e.g., Lodieu et al 2009;Martín et al 2010), important for determination of the substellar initial mass function.…”
Section: Introductionmentioning
confidence: 99%